Appearances Are Deceptive: Two Case Reports in Teenagers on the Conservative Laparoscopic Surgery for Adnexal Torsion with Apparent Infarction - A. Jayawardane; M. Patabendige; C. Gunathilaka (Hindawi Limited, 2022)
Introduction. Torsion of the ovary, tube, or both is estimated to be responsible for 2-7% of all gynaecological emergencies. Oophorectomy is commonly performed for adnexal torsion with a possible negative impact on fertility in women of reproductive age. Case Presentations. We report two cases of teenage girls presented with adnexal torsion describing their laparoscopy features. Detorsion without additional surgical intervention could save their ovaries. Discussion. Detorsion is a more conservative surgical approach that should be considered in all younger women with ovarian torsion.